2020
DOI: 10.17159/sajs.2020/6535
|View full text |Cite
|
Sign up to set email alerts
|

Estimating soil moisture using Sentinel-1 and Sentinel-2 sensors for dryland and palustrine wetland areas

Abstract: Soil moisture content (SMC) plays an important role in the hydrological functioning of wetlands. Remote sensing shows potential for the quantification and monitoring of the SMC of palustrine wetlands; however, this technique remains to be assessed across a wetland–terrestrial gradient in South Africa. The ability of the Sentinel Synthetic Aperture Radar (SAR) and optical sensors, which are freely available from the European Space Agency, were evaluated to predict SMC for a palustrine wetland and surrounding te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Measurements through the spectroradiometer were conducted on 26-27 th January, 28 th February-2 nd March, 24-25 th March, 30-31 st March, and 4-5 th April 2022. [21][22]. The bands used are bands with a spatial resolution of 10 m and 20 m; consequently, the band with a resolution of 60 m is not used.…”
Section: Field Data Collectionmentioning
confidence: 99%
“…Measurements through the spectroradiometer were conducted on 26-27 th January, 28 th February-2 nd March, 24-25 th March, 30-31 st March, and 4-5 th April 2022. [21][22]. The bands used are bands with a spatial resolution of 10 m and 20 m; consequently, the band with a resolution of 60 m is not used.…”
Section: Field Data Collectionmentioning
confidence: 99%
“…For different model-based approaches, retrieving SSM data requires a fusion of the data. The fusion of Sentinel-1 and Sentinel-2 satellite data showed successful applications and accurate results whether in global or field-based SMM estimations [165][166][167][168][169]. There are several different machine learning or empirical-based approaches for this purpose: the Water cloud model [149,168,170,171], change detection method [65,169,172], ANN [149], cost function [173], and support vector regression [174].…”
Section: Remote Sensing Of Soil Moisture In Droughtmentioning
confidence: 99%
“…Advances in satellite technology, data processing, and petrophysics ensure that these techniques will be increasingly important in the future. Many studies have used satellite data, such as the Sentinel and Landsat series, to observe and predict soil properties such as pH [21,22], cation exchange capacity [22], soil organic carbon [22,23], soil organic matter [21,24], clay content [21,22,24], salinity [25], and soil water content estimation [26][27][28][29][30][31][32]. Reference [24] showed that using Sentinel-2 satellite data to identify differences in soil properties can guide on-ground soil sampling and significantly reduce the time and cost of conventional sampling efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Sentinel-2 satellites have been especially useful for soil characterization; data from these satellites are relatively high resolution, contain red-edge band data, and have a 10-day re-visit frequency for the single satellite and 5-day for two satellites under cloud-free conditions [33,34]. The main disadvantage of Sentinel-2 data for soil characterization is that the resolution is currently insufficient for some types of precision agriculture, as the spatial resolution ranges from 10 m to 60 m [31,35]. Additionally, the penetration depth for the Sentinel-2 is also relatively shallow (~5 cm in most soils) [26,31], and estimation of some soil properties is less effective if the vegetation is extensive [21][22][23][24]31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation